PENGARUH K3 (KESELAMATAN DAN KESEHATAN KERJA) DAN DISIPLIN KERJA TERHADAP KINERJA PEKERJA SUB KONTRAKTOR - Daffa, Ibnu Azmi; Adi, Agung Nugroho (Jurnal Kewirausahaan dan Inovasi, 2022)
This study aims to determine the effect of K3 (Occupational Safety and Health) and work discipline simultaneously or partially on the performance of sub-contractor workers in the BRI Malang Regional Office Building project. This type of research is explanatory re-search known as testing the hypothesis to determine the effect of the independent varia-bles, namely K3 (Occupational Safety and Health) (X1) and Work Discipline (X2) on the dependent variable Performance (Y) which use a quantitative approach. This study used a sample of 50 respondents. The hypothesis test in this study used multiple linear regression analysis. The study results explained that K3 (Occupational Safety and Health) and work discipline had a simultaneous effect on worker performance, K3 (Occupational Health and Safety) did not affect performance, and work discipline had a positive impact on perfor-mance. Suggestions from this research are PT. Adhi Karya (Persero) Tbk. The Department of Building is supposed to be able to maintain or even improve the implementation and supervision of K3 (Occupational Health and Safety) and the discipline of the workers to produce a better performance on the PT. Adhi Karya (Persero) Tbk. Department of Build-ing in the future.